2003
DOI: 10.1179/026708303225009300
|View full text |Cite
|
Sign up to set email alerts
|

Galvanisability of silicon free CMnAl TRIP steels

Abstract: Transformation induced plasticity (TRIP) steels are a promising solution for the production of cars with low body mass because of the combination of high strength and large uniform elongation that they offer. However, conventional CMnSi TRIP steels with more than 1 wt-%Si have the drawback of poor Zn coating quality after continuous galvanising. This problem is due to the presence of complex Si ± Mn oxides on the strip surface. The present research work therefore focused on the full substitution of Si by Al in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 6 publications
0
55
0
Order By: Relevance
“…18) In fact, it has been found that steels with contents of up to 1.5 % Al can be successfully galvanized. 10,19,20) Mahieu et al found that Al, like Si, form ironaluminum-oxides, but these do not affect the coatability of low-Si steels. 11) On the contrary, Al has the ability to prevent Si from segregating to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…18) In fact, it has been found that steels with contents of up to 1.5 % Al can be successfully galvanized. 10,19,20) Mahieu et al found that Al, like Si, form ironaluminum-oxides, but these do not affect the coatability of low-Si steels. 11) On the contrary, Al has the ability to prevent Si from segregating to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…8) According to Meyer,9) the partial replacement of Si by Al in TRIP steels results in a much improved galvanisability. Maki 10) also conducted research on the galvanisability of Sifree CMnAl and Al-free CMnSi TRIP steels respectively and similar results were obtained. Furthermore, the mechanical properties of cold rolled Si free CMnAl TRIP steel were comparable to those of conventional CMnSi TRIP steels.…”
Section: Introductionmentioning
confidence: 54%
“…Maki also conducted research on the galvanizability of Si-free CMnAl and Al-free CMnSi TRIP steels respectively and similar results were obtained. 9) Furthermore, the mechanical properties of cold rolled Si free CMnAl TRIP steel were comparable to those of conventional CMnSi TRIP steels.…”
Section: Introductionmentioning
confidence: 63%